Fighting Salmonella Infantis: bacteriophage-driven cleaning and disinfection strategies for broiler farms - Sevilla-Navarro, Sandra; Torres-Boncompte, Jan; Garcia-Llorens, Josep; Bernabéu-Gimeno, Mireia; Domingo-Calap, Pilar; Catalá-Gregori, Pablo (Frontiers in Microbiology, 2024)
Salmonella is a bacterium that can cause food-borne infections and is responsible for the most common gastrointestinal illnesses. The emergence of multi-drug resistant (MDR) strains worldwide is a major threat, representing a major challenge in public health. To reduce its incidence, the One Health approach is required, and the development of new biocontrol protocols will help prevent or eliminate the spread of Salmonella. Prevention measures, such as on-farm cleaning and disinfection protocols, are a crucial step in reducing infection to new flocks and eliminating bacteria that remain in the facilities. However, MDR Salmonella species, such as S. Infantis, are highly resistant to conventional cleaning and disinfection protocols, with an increased ability to persist in the broiler farm environment. The need for alternative biocontrol methods has led to the use of bacteriophages or phages, viruses that target bacteria, as promising tools. Thus, the aim of this study was to evaluate the efficacy of phages as a biocide against S. Infantis isolates in combination with cleaning and disinfection protocols in 10 commercial poultry farms. All commercial farms selected in this study had persistent Salmonella, even after the routinely used cleaning and disinfection procedures. In addition, Salmonella isolated before treatment were phenotypically characterized by antimicrobial resistance patterns. The results showed that 100% of S. Infantis were resistant to at least one antibiotic, and >70% were MDR. Phages were then isolated against the in-farm bacteria, purified, and multiplied for each poultry farm. The cleaning and disinfection protocols included the application of the lytic phages (vB_Si_CECAV_FGS009; vB_Si_CECAV_FGS017; vB_Si_CECAV_FGS029 and vB_Si_CECAV _FGS030) twice at 24-hour intervals between cleaning and disinfection. Following the cleaning and disinfection procedures, Salmonella detection was reduced from 100% after cleaning to 36% after applying the phages and dropped to 0% after the final step of disinfection, thus eliminating Salmonella from the farm facilities. This study demonstrates that bacteriophage application after cleaning and before disinfection enhances the removal of MDR Salmonella Infantis in commercial broiler farms, suggesting their use as biocontrol agents to reduce Salmonella, a major public health concern.